Sampling desing for larval density computation of Aedes Aegypti and Aedes albopictus in the State of S. Paulo, Brazil - Alves, Maria Cecília G.P. (1991)
The Yellow Fever and Dengue Vector Control Program developed by the Superintendency for the Control of Endemic Diseases in the State of S. Paulo recommends Aedes aegypti and Aedes albopictus larval density monitoring in cities with domiciliar infestation. The sampling plan which has been applied in the countries of the Presidente Prudente region (SP- Brazil) since 1987 is described. The infestation is measured by using the Breteau Index. A sample of buildings is drawn, monthly and independently, in the infested cities, in which measurements are to be made. The sample is stratified and the elementary unit selection is made by using two-stage cluster sampling: of blocks and buildings. The sample sizes were defined using the coefficient of variation and the intraclass correlation as estimated for towns covered by the Regional Health Service of S. José do Rio Preto. These sizes must be corrected periodically in accordance with the values of the Breteau Index and its variance obtained in previous months.